2008
DOI: 10.3174/ajnr.a1351
|View full text |Cite
|
Sign up to set email alerts
|

Territorial and Microvascular Perfusion Impairment in Brain Arteriovenous Malformations

Abstract: BACKGROUND AND PURPOSE:Both the existence and clinical relevance of a steal phenomenon in brain arteriovenous malformations (AVMs) remains a matter of debate. This study aimed to assess perfusion in the brain adjacent to brain AVMs and to relate these to macrovascular blood flow in a single measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…6 Reanalysis of these data by using regional flow quantification as used in this study demonstrated the following arterial feeding and venous draining peak velocities in 3 SMG groups: SMG ϭ 1 A previous DSC PWI study demonstrated AVM steal based on significantly higher Hi/Hc ratios of CBF and CBV in 19 patients with AVMs in comparison with healthy subjects. 14 Fiehler et al 25 reported decreased perfusion ratios between affected and nonaffected hemispheres in the MCA and PCA territories accounting for AVM steal. In our study, there were significantly lower perinidal CBF and CBV ratios compared with the remote ratios indicating presence of perinidal hypoperfusion ("AVM steal").…”
Section: Discussionmentioning
confidence: 99%
“…6 Reanalysis of these data by using regional flow quantification as used in this study demonstrated the following arterial feeding and venous draining peak velocities in 3 SMG groups: SMG ϭ 1 A previous DSC PWI study demonstrated AVM steal based on significantly higher Hi/Hc ratios of CBF and CBV in 19 patients with AVMs in comparison with healthy subjects. 14 Fiehler et al 25 reported decreased perfusion ratios between affected and nonaffected hemispheres in the MCA and PCA territories accounting for AVM steal. In our study, there were significantly lower perinidal CBF and CBV ratios compared with the remote ratios indicating presence of perinidal hypoperfusion ("AVM steal").…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that this parameter enables the discrimination of feeding arteries and draining veins of an AVM. 15 Fiehler et al 16 found that the degree of the AVM perfusion steal effect is negatively correlated with the affected/ nonaffected TTP ratio. This ratio was used in this work as an indirect measure of blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] For quantitative estimation of the blood flow transit times through the AVM nidus, a neuroradiologist (T.I.) placed a voxel of interest in the main feeding artery and main draining vein as close to the AVM nidus as possible ( Figure 1) as well as in the corresponding vessels on the contralateral hemisphere in the axial slices of the 4D MRA dataset.…”
Section: Inflow Time Measurement and Quantificationmentioning
confidence: 99%